Maternal clinical characteristics and perinatal outcomes among pregnant women with coronavirus disease 2019. A systematic review. Issue 39 (January 2021) - Novoa, Rommy H.; Quintana, Willy; Llancarí, Pedro; Urbina-Quispe, Katherine; Guevara-Ríos, Enrique; Ventura, Walter
Abstract: Objective: To describe the maternal clinical characteristics, maternal and perinatal outcomes in COVID-19-positive pregnant women. Methods: Articles in all languages on the SARS-CoV-2 infection in pregnant women were sought from MEDLINE, EMBASE, Cochrane Library and LILACS; China National Knowledge Infrastructure Database (CNKI), Chinese Science and Technology Periodical Database (VIP) and Wan Fang Data between December 1, 2019 and April 27, 2020. Bulletins and national reports were also searched. Results: From 12, 168 retrieved articles, 143 were selected for full-text assessment; 33 for descriptive analyses, and 4 case-controls for meta-analysis. In 322 infected pregnant women, aged 20–45 years, the most frequent maternal comorbidity was obesity (24.2%). Forty-two (28.4%) were asymptomatic at admission. Cough (n = 148, 59.7%) and fever (n = 147, 59.3%) were the most prevalent symptoms. In the meta-analysis, fever (OR: 0.13, 95% CI 0.05 to 0.36) and cough (0.26, 95% CI 0.11 to 0.59) were lower in pregnant women with COVID-19 than non-pregnant women with COVID-19.195 (60.6%) delivered, and 125 (38.8%) remained pregnant during the study. Cesarean was reported in 99 (50.8%) women and vaginal delivery in 64 (32.8%). The main adverse obstetric outcome was premature birth (n = 37, 18.9%). Thirty patients (10.3%) with COVID-19-related complications required intensive care, one (0.3%) died. SARS-CoV-2 was absent in breast milk, amniotic fluid, placenta or umbilical cord blood. Conclusions: The maternal clinical characteristics of COVID-19-positive pregnant include frequently fever and cough; however significantly less frequently than non-pregnant women with COVID-19. Iatrogenic preterm birth is the main adverse obstetric outcome. Current data does not support vertical transmission in the third trimester. Highlights: Pregnant women with COVID-19 are less symptomatic than general population. The usual symptoms are fever and cough. The severe morbidity and mortality are similar to those reported for non-pregnant women. The main adverse obstetric outcome is iatrogenic preterm birth. Vertical transmission is unlikely at least in the third trimester.